2023
DOI: 10.1002/advs.202302203
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Transcription Factor RUNX1 is Essential for Promoting Macrophage–Myofibroblast Transition in Non‐Small‐Cell Lung Carcinoma

Philip Chiu‐Tsun Tang,
Max Kam‐Kwan Chan,
Jeff Yat‐Fai Chung
et al.

Abstract: Macrophage‐myofibroblast transition (MMT) is a newly discovered pathway for mass production of pro‐tumoral cancer‐associated fibroblasts (CAFs) in non‐small cell lung carcinoma (NSCLC) in a TGF‐β1/Smad3 dependent manner. Better understanding its regulatory signaling in tumor microenvironment (TME) may identify druggable target for the development of precision medicine. Here, by dissecting the transcriptome dynamics of tumor‐associated macrophage at single‐cell resolution, a crucial role of a hematopoietic tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…In the present study, we demonstrate firstly that immediate administration of RUNX1 inhibitor Ro5-3335 following MI reduces infarct size in rats in vivo and the beneficial effects are associated with repressed cardiac cathepsin levels. Notably, although the RUNX1 inhibitor Ro5-3335 is known to inhibit RUNX1 function and this effect is well evidenced (Cunningham et al 2012 ; Martin et al 2023 ; Delgado-Tirado et al 2020 ; Tang et al 2024 ; Klase et al 2014 ; She et al 2023 ; O'Hare et al 2021 ), the mechanism of inhibition (whether it’s direct or indirect) is under debate. Whilst Cunningham et al (Cunningham et al 2012 ) reported that the inhibitory effect of Ro5-3335 is direct via bindings to both subunits of the RUNX1 heterodimeric transcription factor complex which is indicated by UV measurement of protein binding, a later study by Illendula et al (Illendula et al 2016 ) pointed out that the effect of Ro5-3335 on RUNX1 function may be indirect because its interaction with the RUNX1 runt domain could not be detected by NMR and suggested that the inhibitory effect of Ro5-3335 may be based on the inhibition of SMARCA2 which is predicted to be an interaction partner of RUNX1 by protein-protein interaction prediction program PIPS (Illendula et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we demonstrate firstly that immediate administration of RUNX1 inhibitor Ro5-3335 following MI reduces infarct size in rats in vivo and the beneficial effects are associated with repressed cardiac cathepsin levels. Notably, although the RUNX1 inhibitor Ro5-3335 is known to inhibit RUNX1 function and this effect is well evidenced (Cunningham et al 2012 ; Martin et al 2023 ; Delgado-Tirado et al 2020 ; Tang et al 2024 ; Klase et al 2014 ; She et al 2023 ; O'Hare et al 2021 ), the mechanism of inhibition (whether it’s direct or indirect) is under debate. Whilst Cunningham et al (Cunningham et al 2012 ) reported that the inhibitory effect of Ro5-3335 is direct via bindings to both subunits of the RUNX1 heterodimeric transcription factor complex which is indicated by UV measurement of protein binding, a later study by Illendula et al (Illendula et al 2016 ) pointed out that the effect of Ro5-3335 on RUNX1 function may be indirect because its interaction with the RUNX1 runt domain could not be detected by NMR and suggested that the inhibitory effect of Ro5-3335 may be based on the inhibition of SMARCA2 which is predicted to be an interaction partner of RUNX1 by protein-protein interaction prediction program PIPS (Illendula et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al summarized the dynamics and therapeutic potentials of tumor-associated macrophages in solid cancer, such as a novel neuron type derived from "Macrophage to Neuron-like Cell Transition" in lung cancer (Figure 1) (8). Single-cell RNAsequencing allows researchers to dissect the TME in a cell-type specific manner, therefore the contributions of fibrotic signaling in the cancer immunity which was hidden in the conventional bulk sequencing at population level can be unmasked (9).…”
Section: Therapeutic Developmentmentioning
confidence: 99%